Physical Health Outcomes of Trauma Exposure Across the Lifespan - Wamser, Rachel A. (Journal of interpersonal violence, 2023)
Trauma exposure and posttraumatic stress symptoms (PTSS) are established risk factors for poorer physical health. Prior work has focused on childhood adversities and PTSS in relation to physical health conditions, but trauma exposure over the lifespan has been overlooked. Further, the associations between trauma and PTSS and other physical health markers, such as diet and exercise, are less clear. Very little is known regarding how different trauma types (i.e., interpersonal, non-interpersonal), may be tied to aspects of physical health. To expand this area of research, this study aimed to: (a) examine the links between cumulative trauma and PTSS, and body mass index (BMI), diet, and exercise; and (b) investigate the relations between interpersonal and non-interpersonal trauma and these three health indices, while controlling for PTSS. Participants were 493 Midwestern University students (Mage = 23.87, standard deviation [SD] = 6.90, range = 18–63; 79.3% female; 57.4% White). Cumulative trauma corresponded with higher BMIs and less exercise use (B = 0.10; B = −0.09), while PTSS were unrelated. Conversely, PTSS were tied to greater consumption of added sugars (B = 0.11), and cumulative trauma was not linked with diet. Interpersonal and non-interpersonal traumas were not tied to BMI or exercise, although interpersonal trauma and PTSS were linked with greater sugar intake and non-interpersonal trauma was associated with fruit and vegetable consumption. Trauma exposure and PTSS may have complicated and distinct associations with physical health indices, such as BMI, diet, and exercise, and additional research is needed to further parse out these relations.